Mapping Surface Variability of the Central Sulcus in Musicians - Li, Shuyu; Han, Ying; Wang, Deyi; Yang, Hong; Fan, Yubo; Lv, Yating; Tang, Hehan; Gong, Qiyong; Zang, Yufeng; He, Yong (Cerebral cortex (New York, N.Y. 1991), 2010)
We employed a sulcal geometry-based approach to investigate the morphology of the central sulcus (CS) in musicians (pianists). The anterior and posterior walls of the CS were first manually outlined from high-resolution magnetic resonance (MR) images of 41 right-handed subjects (20 musicians and 21 controls), followed by a surface reconstruction and parameterization procedure to ensure the anatomical correspondence of surface locations across subjects. The intrasulcal length, surface area, and local variability of the CS were measured. There were no significant differences in either the intrasulcal length or surface area of the anterior or posterior walls between the 2 groups. However, we observed that the controls had a pronounced left-larger-than-right asymmetry that was reduced in the musicians. Importantly, we found that the musicians showed greater local variability in the middle section (i.e., somatotopic hand area) of the right CS and the lower section of the left CS as compared with the controls. Further analysis revealed significantly negative correlations between the variability of the middle section of the right CS and the age of commencement of musical training. Our findings suggest that the musicians might be associated with plastic changes in the 3D morphology of the CS in response to long-term motor skill training.